The medieval presence in the modernist aesthetic : unattended moments - Marshall, Simone Celine.; Cusack, Carole M., 1962- (Studies in Religion and the Arts, 2017)
In The Medieval Presence in the Modernist Aesthetic: Unattended Moments , editors Simone Celine Marshall and Carole M. Cusack have brought together essays on literary Modernism that uncover medieval themes and tropes that have previously been "unattended", that is, neglected or ignored. A historical span of a century is covered, from musical modernist Richard Wagner's final opera Parsifal (1882) to Russell Hoban's speculative fiction Riddley Walker (1980), and themes of Arthurian literature, scholastic philosophy, Irish legends, classical philology, dream theory, Orthodox theology and textual exegesis are brought into conversation with key Modernist writers, including T. S. Eliot, Ezra Pound, Samuel Beckett, Marcel Proust, W. B. Yeats, Evelyn Waugh and Eugene Ionesco. These scholarly investigations are original, illuminating, and often delightful.